Biomedical Approach to Developing and Characterizing Chitosan Nanoparticles Encapsulating Urapidil for Hypertension Management - V. Tulasi; A. Saritha (International Journal of Biomedical Innovations and Engineering, 2024)
The aim of this study was to create Chitosan Nanoparticles loaded with Urapidil to achieve controlled drug release, enhance solubility, and reduce dosing frequency to improve patient adherence to therapy for hypertension. Urapidil was formulated into nanoparticles via the ionic-gelation method using Chitosan as a polymer, Sodium tripolyphosphate as a cross-linking agent, and filled into hard gelatin capsules after lyophilization. Pre-formulation studies, including melting point analysis and determination of the absorption maximum at 268 nm, confirmed the drug and excipients' stability, safety, and effectiveness within the specified range. Urapidil-loaded chitosan nanoparticles were prepared using various concentrations of chitosan (0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, and 0.5%), with sodium tripolyphosphate serving as a cross-linking agent and Tween 80 acting as a de-aggregating agent. Characterization of all seven formulations revealed a percentage yield within the range of 78.84 to 87.25% and entrapment efficiency between 83.40 and 93.15%, with higher concentrations of polymer resulting in increased entrapment efficiency. Solubility analysis showed improvement after formulation, with the solubility of formulation F5 increased to 9.4933 mg/ml in distilled water and 13.251 mg/ml in phosphate buffer pH 6.8. In vitro release studies demonstrated controlled release with formulation F5 releasing 95.03% of the drug after 12 h. This formulation was selected as the optimized one due to its higher entrapment efficiency, drug content, and prolonged drug release profile. Accelerated stability tests revealed no notable changes in the appearance, drug content, or entrapment efficiency of formulation F5 after 90 days under various storage conditions. Among all formulations, F5, with a 0.3% chitosan concentration, proved to be the most effective for achieving controlled drug release.
Keywords: Chitosan Nanoparticles; Formulation; Urapidil; biomedical; characterization